2007
DOI: 10.1158/0008-5472.can-07-0320
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis Identifies Imidazo[1,2-b]Pyridazines as PIM Kinase Inhibitors with In vitro Antileukemic Activity

Abstract: Much attention has recently been focused on PIM kinases as potential targets for the treatment of hematopoietic malignancies and some solid cancers. Using protein stability shift assays, we identified a family of imidazo [1,2-b]pyridazines to specifically interact with and inhibit PIM kinases with low nanomolar potency. The high-resolution crystal structure of a PIM1 inhibitor complex revealed that imidazo[1,2-b]pyrridazines surprisingly interact with the NH 2 -terminal lobe helix AC rather than with the kinas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
202
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 183 publications
(210 citation statements)
references
References 47 publications
8
202
0
Order By: Relevance
“…To further test the hypothesis that PIM1 kinase activity is involved in regulation of CXCR4 surface expression, we used a recently identified potent small molecule inhibitor of human PIM1 (K00486; Pogacic et al, 2007). Human JURKAT acute lymphoblastic leukemia cells that express high levels of PIM1 and surface CXCR4 were used in this experiment.…”
Section: Resultsmentioning
confidence: 99%
“…To further test the hypothesis that PIM1 kinase activity is involved in regulation of CXCR4 surface expression, we used a recently identified potent small molecule inhibitor of human PIM1 (K00486; Pogacic et al, 2007). Human JURKAT acute lymphoblastic leukemia cells that express high levels of PIM1 and surface CXCR4 were used in this experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, small molecule inhibitors of the Pim-1 kinase have been recently described in vitro and in cell-based systems. [33][34][35] Targeting the Pim-1 kinase may be a beneficial addition to a traditional cancer chemotherapy regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the importance of the microenvironment, and especially the presence of stromal cells, for the survival of CLL cells (10,42). The interaction between BMSCs and CLL cells induces a protective microenvironment blocking the proapoptotic effect of various chemotherapeutical agents and spontaneous apoptosis in vitro.…”
Section: Pim Kinase Inhibition With Three Different Pim Inhibitors Inmentioning
confidence: 99%
“…K00135 and K00486, two imidazo[1,2-b]pyridazines, show low IC 50 values for inhibition of PIM1 and PIM2 kinase activity, and have shown proapoptotic effects in AML cells (37,42). The third PIM kinase inhibitor, A47, is based on another chemical structure, a furan thiazolidin, and inhibits all three PIM kinases in low micromolar concentrations including PIM3 (39).…”
Section: Pim Kinase Inhibition With Three Different Pim Inhibitors Inmentioning
confidence: 99%